Results of the truck strike (2018): a hybridism of bilionary statistics and diesel oil in the face of macroeconomics (Research, Society and Development, 2019)
The present work uses a literature review in order to present characteristics and information related to direct impacts directly generated in the Brazilian economy in the face of a fuel crisis linked to the event of the truck drivers' strike. This crisis affected the main economic points triggered by the phenomenon of the demonstrators of the truck drivers in the federal and state highways of Brazil. The general objective of the study is to synthesize information through political and economic references. So they will discuss the data losses the most relevant macroeconomic preliminarily - and therefore understand the phenomenon of strike by truckers and their direct relationship in the economic chain when there is high dependence on road service under alert grievances that will pass for a long time. The result of the most expressive social movement in the first half of 2017 through a research of quantitative nature, descriptive research technique under research methods: statistical, historical and comparative. The statistical survey comes from the following sources: main magazines, newspapers, specialists, specialized data platforms. On the context, one can understand how much downtime influenced Brazil's economy, as well as have the possibility to create a parameter to the socioeconomic dimensions triggered by such phenomena. Data show that losses ranged from R $ 75 billion to R $ 100 billion. In view of the strike, expected financial market inflation from 3.65% to 3.82%, and the Gross Domestic Product (GDP) decline dropped from 2.18% to 1.94% this year (2018).